Characterization of Aspergillus spp. isolated from patients with coronavirus disease 2019. Issue 6 (June 2023) - Ogawa, Masashi; Niki, Makoto; Imoto, Waki; Dobashi, Akane; Imai, Minami; Takayama, Naomi; Mitani, Kei; Kakuno, Shigeki; Shibata, Wataru; Yamada, Koichi; Kakeya, Hiroshi
Abstract: Introduction: Invasive pulmonary aspergillosis (IPA) is an important complication of coronavirus disease 2019 (COVID-19), and while there are case reports and epidemiological studies, few studies have isolated Aspergillus strains from patients. Therefore, we analyzed the strains, sensitivities, and genetic homology of Aspergillus spp . Isolated from patients with COVID-19. Methods: We investigated the Aspergillus strains detected from patients with COVID-19 hospitalized in Osaka Metropolitan University Hospital from December 2020 to June 2021. A molecular epidemiological analysis of Aspergillus spp. was performed using drug susceptibility tests and TRESPERG typing, and data on patient characteristics were collected from electronic medical records. Results: Twelve strains of Aspergillus were detected in 11 of the 122 patients (9%) with COVID-19. A. fumigatus was the most common species detected, followed by one strain each of Aspergillus aureolus, Aspergillus nidulans, Aspergillus niger, and Aspergillus terreus . A. aureolus was resistant to voriconazole, and no resistance was found in other strains. All A. fumigatus strains were genetically distinct strains. Six of the 11 patients that harbored Aspergillus received antifungal drug treatment and tested positive for β-D-glucan and/or Aspergillus galactomannan antigen. The results indicated that Aspergillus infections were acquired from outside the hospital and not from nosocomial infections. Conclusion: Strict surveillance of Aspergillus spp. is beneficial in patients at high-risk for IPA. When Aspergillus is detected, it is important to monitor the onset of IPA carefully and identify the strain, perform drug sensitivity tests, and facilitate early administration of therapeutic agents to patients with IPA.